KADAR HbA1c DAN RASIO LIPID PADA WANITA DEWASA DENGAN OBESITAS SENTRAL - Lisa Sudaryanto; Laurensius Imus Ventora; Fenty Fenty (Sanata Dharma University, 2015)
Central obesity was accumulation of fat in the abdominal region. Many studies showed correlations between central obesity and cardiovascular diseases, e.g. diabetes and dyslipidemia. This study was conducted to know the difference between HbA1c and lipid profil between the women with and without central obesity. This study was an analytic observational study with cross-sectional design. Subjects of 52 respondents were healthy adult women staff in campus I, II, III Sanata Dharma University in Yogyakarta and selected using purposive sampling technique. The data of waist circumference, pelvic/hip circumference, HbA1c and lipid profile were collected among the subjects and analyzed with computer with 95% confidence interval. The results of this study showed HbA1c levels and lipid profile were different between the women with and without central obesity, although the difference was not statistically significant.